Analysis of Termination of Employment Due to Violation of Collective Labor Agreement (Case Study of Decision Number 1326 K/Pdt.Sus-Phi/2023) - Satrio Hadi Baskoro; Nugroho, Arinto (Universitas Negeri Surabaya, 2024)
Termination of employment carried out by PT Medicinal Cosmetic Industries Indonesia to Tri Dewi Purnama Sari on the grounds of violating the Joint Work Agreement resulted in a dispute between the two until the issuance of Supreme Court Decision Number: 1326 K/Pdt.SusPHI/2023. This layoff was carried out by violating labor law due to the existence of a clause in the Joint Work Agreement that was not in accordance with the development of legislation. The difference between the decision of the first instance panel of judges stating that the plaintiff's lawsuit was partially granted and the decision of the Supreme Court of Cassation which stated that the defendant's lawsuit was granted in full resulted in a significant difference in the judge's perspective, considerations, and the provision of the basis for the decision to resolve the dispute that occurred. This study aims to examine the legal considerations (ratio decidendi) used by the Panel of Judges in deciding the dispute and to find out the appropriate case resolution in deciding the dispute. The type of research used in this study is normative legal research conducted through literature review or secondary data. The results of this study indicate that there are errors in the interpretation of the collective work agreement and the calculation of severance pay for workers who are laid off.